Fabrication and moulding of cellular materials by rapid prototyping. (1st September 2004) - Stampfl, J.; Fouad, H.; Seidler, S.; Liska, R.; Schwager, F.; Woesz, A.; Fratzl, P.
Many biological materials (e.g. wood, cork, bone, etc) are based on cellular designs, since cellular architectures offer the possibility to optimise the properties (stiffness, density, strength, etc) of a structure according to the environmental conditions the structure is exposed to. By using rapid prototyping, it is possible to fabricate cellular materials on a similar size scale as in natural material-structures. By using appropriate moulding techniques, these structures can be fabricated out of a wide variety of materials (polymers, ceramics, composites). In this work, several RP techniques are investigated regarding their suitability for the fabrication of cellular solids. The main focus is on using direct light projection (stereolithography) in combination with gelcasting as moulding technique. Besides using commercial light-sensitive resins, a class of newly developed water-soluble resins has been evaluated regarding its usability as sacrificial mould material.